Pengabdian Masyarakat International Workshop Kemandirian Anak-Anak Penyandang Disabilitas dalam Daily Living (Aku Bukan Sampah) Bersama SRC Holland untuk Masyarakat Indonesia - Chandra Lukita; Amroni Amroni; Aan Kanivia; Lena Magdalena; Ridho Taufiq Subagio; Turini Turini; Agus Sevtiana; Wiwiek Nurkomala Dewi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Children with disabilities in Indonesia still face various challenges in achieving independence in everyday life. Special attention is needed to provide adequate support so that they can overcome these obstacles and achieve their rights with dignity. The main focus of this international PkM activity is to introduce innovative methods and strategies that can increase their independence, with the main message "I'm Not Trash" as a call to recognize and respect the rights of children with disabilities. The aim of this activity is to increase the independence of children with disabilities in living their daily lives. The method of this international PkM activity is delivery of material, question and answer and evaluation. The result of this activity is an increase in the independence of children with disabilities in aspects of daily life. They gain new skills, both in caring for themselves, participating in daily activities, and in managing their lives independently.